Conversion between Mini‐Mental State Examination, Montreal Cognitive Assessment, and Dementia Rating Scale‐2 scores in Parkinson's disease. Issue 14 (7th November 2014) - van Steenoven, Inger; Aarsland, Dag; Hurtig, Howard; Chen‐Plotkin, Alice; Duda, John E.; Rick, Jacqueline; Chahine, Lama M.; Dahodwala, Nabila; Trojanowski, John Q.; Roalf, David R.; Moberg, Paul J.; Weintraub, Daniel
ABSTRACT Cognitive impairment is one of the earliest, most common, and most disabling non‐motor symptoms in Parkinson's disease (PD). Thus, routine screening of global cognitive abilities is important for the optimal management of PD patients. Few global cognitive screening instruments have been developed for or validated in PD patients. The Mini‐Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Dementia Rating Scale‐2 (DRS‐2) have been used extensively for cognitive screening in both clinical and research settings. Determining how to convert the scores between instruments would facilitate the longitudinal assessment of cognition in clinical settings and the comparison and synthesis of cognitive data in multicenter and longitudinal cohort studies. The primary aim of this study was to apply a simple and reliable algorithm for the conversion of MoCA to MMSE scores in PD patients. A secondary aim was to apply this algorithm for the conversion of DRS‐2 to both MMSE and MoCA scores. The cognitive performance of a convenience sample of 360 patients with idiopathic PD was assessed by at least two of these cognitive screening instruments. We then developed conversion scores between the MMSE, MoCA, and DRS‐2 using equipercentile equating and log‐linear smoothing. The conversion score tables reported here enable direct and easy comparison of three routinely used cognitive screening assessments in PD patients. © 2014 International Parkinson and Movement Disorder Society